New pathological findings in emphysema of childhood: 1. Polyalveolar lobe with emphysema. Issue 6 (November 1970) - Hislop, Alison; Reid, Lynne
Abstract : A new pathological entity is here described—a polyalveolar lobe with or without emphysema—giving rise to the clinical features of childhood lobar emphysema. A detailed and quantitative study of the airways, alveoli and arteries was carried out on the left upper lobe removed because of shortness of breath, thought to be due to `childhood lobar emphysema'. The child was 17 days old and the radiograph showed hypertransradiancy of the left lung. The alveolar number was increased five-fold. Alveolar size was normal, so it was found that emphysema, accepted today as a structural diagnosis, was not present. The increase in alveolar number seemed confined to the apical, posterior, and anterior segments, the lingula being unaffected. By contrast, the airways and arteries were normal for age in number, size and structure, suggesting that the condition was a `giantism' of the alveolar region. The blood flow was probably too low for the lobar volume; certainly the excessive alveolar number could not be due to increase in blood flow. In two further specimens, previously dissected, a similar polyalveolar condition was found, associated with emphysema. The patients were older at the time of surgical resection and the emphysema may have developed post-natally. In all three cases the radiographic features had suggested emphysema. It is suggested that the condition be called `polyalveolar lobe', `with emphysema' or `without emphysema' being added as a separate item to the description.